-m-7=m-1

Simple and best practice solution for -m-7=m-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -m-7=m-1 equation:


m in (-oo:+oo)

-m-7 = m-1 // - m-1

1-m-m-7 = 0

-2*m-6 = 0 // + 6

-2*m = 6 // : -2

m = 6/(-2)

m = -3

m = -3

See similar equations:

| 3-6a=3a-69 | | 50-x=.25 | | 2-4a=7a+68 | | 2m-7=-13+4m | | -5b+2=6b-108 | | -7x+5=17-3x | | -5-7m=5m+127 | | 6n+9=-3+2n | | 2t+10=4t+14 | | 6x+5=2x-43 | | 1-7a=6a-142 | | -3w+2=-10-2w | | 3x+5=-7x-15 | | 6m-10=89-3m | | -6t+2=t+86 | | -5x+8=-16+3x | | -2x+4=5x+4 | | 7k+4=-6k-113 | | 6d+3=4d+17 | | 4-n=5n-14 | | 8+2m=m+8 | | w-9=19-3w | | k-8=7k-20 | | 3m+2=122-7m | | -6w+8=-7w+13 | | -3m+7=-89+5m | | t+2=6t-43 | | 2x+8=48+6x | | 2+2*0= | | |3x-6|=7+|x-2| | | 5b+10=b+42 | | 2d-6=-2d+30 |

Equations solver categories